miR-223-3p Inhibits Antigen Endocytosis and Presentation and Promotes the Tolerogenic Potential of Dendritic Cells through Targeting Mannose Receptor Signaling and Rhob - Hao-Cheng Tang; Yin-Yan Lai; Jing Zheng; Hong-Yan Jiang; Geng Xu (Journal of Immunology Research)
Background. The role of miR-223-3p in dendritic cells (DCs) is unknown. This study is aimed at investigating the effect of miR-223-3p on the antigen uptake and presentation capacities of DCs and the underlying molecular mechanism. Methods. FITC-OVA antigen uptake and cell surface markers in bone marrow-derived DCs (BMDCs) were analyzed by flow cytometry. BMDCs were transfected with the miR-223-3p mimic or inhibitor. Cytokine levels were determined by ELISA. CD4+ T cell differentiation was determined by mixed lymphocyte culture assay. Results. OVA treatment significantly downregulated miR-223-3p in BMDCs. The miR-223-3p mimic significantly inhibited OVA-induced antigen uptake and surface expression of MHC-II on BMDCs (P<0.01). The miR-223-3p mimic increased TGF-β1 production in OVA-treated DCs (P<0.01). Mixed lymphocyte reaction showed that the miR-223-3p mimic significantly promoted Treg cell differentiation. In addition, the miR-223-3p mimic significantly upregulated CD103 in DCs, indicating the promotion of tolerogenic DCs. The miR-223-3p mimic downregulated Rhob protein in OVA-induced DCs. Rhob knockdown significantly suppressed the ability of FITC-OVA endocytosis (P<0.01) and surface MHC-II molecule expression (P<0.01) in BMDCs, promoting promoted Treg cell differentiation. Mannose receptor (MR) knockdown significantly upregulated miR-223-3p, downregulated Rhob protein in OVA-treated DCs, inhibited the FITC-OVA endocytosis and surface MHC-II expression in BMDCs, and promoted Treg cell differentiation (all P<0.01). Conclusion. These data suggest that miR-223-3p has an inhibitory effect on the antigen uptake and presentation capacities of BMDCs and promotes Treg cell differentiation, which is, at least partially, through targeting MR signaling and Rhob.